Integration of Social and Natural Sciences within the Perspective of Hadith - Hidayah, Rohmatun Nurul; Roibin, Roibin (Nursyam Center, 2023)
Integration in the current era occurs a lot because by updating high-level knowledge can develop rapidly. in hadith there are many discussions about social sciences and natural sciences, this article will discuss the integration of social and natural sciences in the perspective of hadith. The implication of natural sciences is that textual understanding is stronger than direct understanding of hadith texts. This adds confidence to the content of the meaning of the hadith which is used as the object of study. This research method uses Library Research with the Factual Historical Model, which examines the substance of texts that contain the thoughts and ideas of figures as religious works as contained in the thoughts and works of figures. Based on the scientific field, this type of research is a qualitative method with religious research, namely academic studies on religion and religiosity. The implication of natural sciences is that textual understanding is stronger than direct understanding of hadith texts. This adds confidence to the content of the meaning of the hadith which is used as the object of study. This implication is different from the social sciences where the understanding of hadith that emerges is contextual understanding. Contextual understanding is understanding that functions to separate meanings that can be applied in various times and places.